Gotowość do emigracji tarnowskich maturzystów w kontekście czynników determinujących skłonność migracyjną młodych Polaków - Wójcik, Dawid; Skowron, Iwona; Satora, Grzegorz (My University, 2012)
Praca służyła pomiarowi skłonności emigracyjnej tarnowskich maturzystów oraz ustaleniu czynników ją determinujących. W tym celu przeprowadzono na przełomie marca i kwietnia 2012 roku badanie wśród uczniów szkół ponadgimnazjalnych na terenie miasta Tarnowa z wykorzystaniem techniki ankiety audytoryjnej. Szczegółowe wyniki i analizy wskazują na wysoką gotowość do wyjazdów zagranicznych tarnowskiej młodzieży. Oszacowano, że w ciągu najbliższych 5 lat około połowa obecnych maturzystów wyjedzie przynajmniej na jakiś czas do innego kraju. Młodzi zamierzają wyjechać głównie w celu zarobkowym. Wśród najważniejszych czynników wpływających na badaną skłonność znalazły się możliwości podjęcia pracy zapewniającej utrzymanie, znajomość języków obcych oraz posiadanie rodziny i znajomych za granicą. Warunki życia nie zachęcają młodych do wiązania swojego przyszłego życia z regionem tarnowskim. Mimo to, jak wynika z przeprowadzonej analizy, większość wyjazdów będzie miała charakter czasowy i prawdopodobnie znaczna część emigrantów po spełnieniu swoich zagranicznych celów powróci do rodzinnych stron.

The objective of the work was to measure the emigration propensity of Tarnów secondary education graduates and to define its determinants. For this purpose at the turn of March and April 2012 a research was carried out among secondary school students within the Tarnów area with the use of the random survey technique. Detailed results and analyses indicate a high level of readiness among Tarnów youth to move abroad. It was estimated that in the next 5 years approximately half of the present-day secondary school graduates will move to another country at least temporally. Young people intend to go mainly for labour reasons. The most significant factors influencing the surveyed propensity included an opportunity to find employment allowing meeting the costs of living, knowledge of foreign languages and having family members and friends abroad. Living conditions do not encourage young people to tie their future with the Tarnów region. Despite this, as it appears from the conducted analysis, the majority of such emigration trips will have a temporary nature and most likely a large percentage of emigrants will return to their homeland after their goals behind a decision to go abroad have been achieved.
Readiness to emigrate among Tarnów’s secondary school graduates in the context of factors determining migration tendency of young Polish people
Keywords: emigracja; młodzież; skłonność migracyjna; exodus; determinanty migracji; emigration; youth; emigration propensity; exodus; determinants of migration